The prevalence of angina symptoms and association with cardiovascular risk factors, among rural, urban and rural to urban migrant populations in Peru - Gilman Robert H; Loret de Mola Christian; Zaman M Justin S; Smeeth Liam; Miranda J Jaime (BMC Cardiovascular Disorders, 2010)
Abstract Background Rural-to-urban migration in low- and middle-income countries causes an increase in individual cardiovascular risk. Cost-effective interventions at early stages of the natural history of coronary disease such as angina may stem an epidemic of premature coronary deaths in these countries. However, there are few data on the prevalence of angina in developing countries, whilst the understanding the aetiology of angina is complicated by the difficulty in measuring it across differing populations. Methods The PERU MIGRANT study was designed to investigate differences between rural-to-urban migrant and non-migrant groups in specific cardiovascular disease risk factors. Mass-migration seen in Peru from 1980s onwards was largely driven by politically motivated violence resulting in less 'healthy migrant' selection bias. The Rose angina questionnaire was used to record chest pain, which was classified definite, possible and non-exertional. Mental health was measured using the General Health Questionnaire (GHQ-12). Mantel-Haenszel odds ratios (adjusted for age, sex, cardiovascular disease risk factors and mental health) were used to assess the risk of chest pain in the migrant and urban groups compared to the rural group, and further to assess the relationship (age and sex-adjusted) between risk factors, mental health and chest pain. Results Compared to the urban group, rural dwellers had a greatly increased likelihood of possible/definite angina (multi-adjusted OR 2.82 (1.68- 4.73)). Urban and migrant groups had higher levels of risk factors (e.g. smoking - 20.1% urban, 5.5% rural). No diabetes was seen in the rural dwellers who complained of possible/definite angina. Rural dwellers had a higher prevalence of mood disorder and the presence of a mood disorder was associated with possible/definite angina in all three groups, but not consistently with non-exertional chest pain. Conclusion Rural groups had a higher prevalence of angina as measured by Rose questionnaire than migrants and urban dwellers, and a higher prevalence of mood disorder. The presence of a mood disorder was associated with angina. The Rose angina questionnaire may not be of relevance to rural populations in developing countries with a low pre-test probability of coronary disease and poor mental health.